Investigating different damages in a hybrid composite plate completely immersed in water using Ultrasonic waves - Masurkar, Faeez (2018)
The present research investigates the ability of ultrasonic waves in detecting and localizing different types of damage in a hybrid metal-composite laminate fully immersed in water through the permanently attached piezoelectric (PZT) transducers (PZT). Based on the wave-structure analysis and dispersion diagrams obtained for the hybrid metal-composite laminate, a suitable wave excitation frequency is selected for conducting numerical simulations. Accordingly, a gaussian-windowed tone burst signal centered at 250 kHz is applied at the PZT to generate ultrasonic waves in the test specimen. It is found that Scholte wave mode is generated and propagates along the water-solid interface in addition to the anti symmetric guided wave modes. Further, mode conversion is observed during the wave mode-damage interaction. Comparing the pristine and damaged specimens, additional wave packets are seen to be propagating within the specimen that is revealed by analyzing the time-domain waveforms. This information can be further utilized in detecting as well as localizing the damage in the specimen. The location of damage found is well in harmony with the physical locations of damage. Thus, the proposed methodology is found to be capable of investigating the health status of immersed hybrid laminates non-destructively using ultrasonic waves with the help of simple and cost-effective PZT sensors.